The Influence of Financial Literacy and Financial Inclusion on Saving Behavior in Manado - Juan Worang; Joy Elly Tulung; Merinda H. C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Abstract: Increased Saving Behavior is an important factor in achieving financial stable and welfare. Increasing saving can be done by increasing the knowledge and benefits of saving. Saving Behavior is the two actions that coincide with the act of saving with the perception of future needs, and carried out to face the financial crisis. Therefore, to increase public saving behavior, it is necessary to know what factors influence this intention, and how they affect it. This study aims to analyze the influence of Financial Literacy and Financial Inclusion on Saving Behavior. The researcher conducted this research through quantitative methods. Multiple Regression Analysis method is used to analyze the influence of the independent variables toward the dependent variable. Sample were taken from the Bank Account holder in Manado with a total sample of 100 respondents. The results of this study indicate that Financial Literacy have a positive and significant influence on Saving Behavior, while Financial Inclusion has not significant effect on Saving Behavior. The results also indicate that Financial Literacy and Financial Inclusion simultaneously influence Saving Behavior positively and significantly. Keywords: financial literacy, financial inclusion, saving behavior.